Argumentation in Multi-Agent Systems Fifth International Workshop, ArgMAS 2008, Estoril, Portugal, May 12, 2008. Revised Selected and Invited Papers - Rahwan, Iyad.; Moraitis, Pavlos; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2009)
During the last decade Argumentation has been gaining importance within Artificial Intelligence especially in multi agent systems. Argumentation is a powerful mechanism for modelling the internal reasoning of an agent. It also provides tools for analysing, designing and implementing sophisticated forms of interaction among rational agents, thus making important contributions to the theory and practice of multiagent dialogues. Application domains include: nonmonotonic reasoning, legal disputes, business negotiation, labor disputes, team formation, scientific inquiry, deliberative democracy, ontology reconciliation, risk analysis, scheduling, and logistics. This volume presents the latest developments in this area at the interface of argumentation theory and multi agent systems. The 10 revised full papers presented together with 3 invited papers from the AAMAS 2008 conference were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on argument-based reasoning, argumentation and dialogue, as well as strategic and pragmatic issues.
Argument-Based Reasoning -- Personality-Based Practical Reasoning -- Argumentation Based Resolution of Conflicts between Desires and Normative Goals -- A Constrained Argumentation System for Practical Reasoning -- An Argumentation Framework Based on Strength for Ontology Mapping -- Contextual Extension with Concept Maps in the Argument Interchange Format -- Argumentation and Dialogue -- Command Dialogues -- Argumentation and Artifact for Dialogue Support -- Co-ordination and Co-operation in Agent Systems: Social Laws and Argumentation -- Annotation and Matching of First-Class Agent Interaction Protocols -- Strategic and Pragmatic Issues -- Argumentation- vs. Proposal-Based Negotiation: An Empirical Case Study on the Basis of Game-Theoretic Solution Concepts -- Argumentation-Based Information Exchange in Prediction Markets -- An Argumentative Approach for Modelling Coalitions Using ATL -- A Dialogue Mechanism for Public Argumentation Using Conversation Policies.
Keywords: Computer science; Computer communication systems; Computer programming; User interfaces (Computer systems).; Computers; Artificial intelligence; Computer simulation; Computer Science; Artificial Intelligence (incl. Robotics).; Computer Communication Networks; Programming Techniques; Simulation and Modeling; Computing Methodologies; User Interfaces and Human Computer Interaction; Electronic books